Islanding Detection of Inverter Based DG Unit Using PV System - M. Divyasree; L.Venkata Narasimha Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Distributed generation (DG) units are rapidly increasing and most of them are interconnected with distribution network to supply power into the network as well as local loads Islanding operations of DG usually occur when power supply from the main utility is interrupted due to several reasons but the DG keeps supplying power into the distribution networks. a new method for islanding detection of inverter-based distributed generation (DG). Although active islanding detection techniques have smaller non detection zones than passive techniques, active methods could degrade the system power quality and are not as simple and easy to implement as passive methods. The phenomenon of unintentional islanding occurs when a distributed generator (DG) continues to feed power into the grid when power flow from the central utility source has been interrupted. A simple islanding detection scheme has been designed based on this idea. The proposed method has been studied under multiple-DG operation modes and the UL 1741 islanding tests. The simulations results, carried out by MATLAB/Simulink, show that the proposed method has a small Non detection zone.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6257